APPLICATION OF WATER-SAVING TECHNOLOGIES IN WINTER WHEAT CULTIVATION - Saksonov, U. S. (INTERNATIONAL CONFERENCES, 2022)
This article provides information on the use of moisture retention hydrogel as a water-saving technology for growing winter wheat in predominantly irrigated fields.